A concise review on the elastomeric behavior of electroactive polymer materials. (3rd May 2021) - Khan, Muhammad; Li, Tiehu; Hayat, Asif; Zada, Amir; Ali, Tariq; Uddin, Ikram; Hayat, Ashiq; Khan, Majid; Ullah, Azeem; Hussain, Amjad; Zhao, Tingkai
Summary: In recent 20 years, electronic equipment has been developing rapidly in the direction of light, miniaturization, flexibility, and integration. It is urgent to meet the needs of matching energy supply system to solve the practical application requirements in the fields of intelligent communication and mobile medical treatment. Electroactive polymers (EAPs) are recommendable material for manifesting muscle‐like actuation. The dielectric elastomers (DEs) obtained from the EAPs are quite capable of inducing electrical energy and transmute it into mechanical energy. DEs are capacitors covered by an outer elastic membrane, sandwiched between the two docile electrodes. In the beginning, for getting the efficient responses out of the DE actuators, the material requirements and electromechanical principal are applied. Viscoelastic damping, low dielectric loss, stretch ability, and dielectric permittivity are the desirable characteristics that we are expecting in a polymer. In the current research, we are going to adopt the sequential approach by describing the advances, challenges, and applications of DEAs in the coming future.